Effects of magnesium deficiency on stress manifestations in women of reproductive age with nonspecific vaginitis - O. D. Riazanova; Н. I. Reznichenko (Zaporožskij Medicinskij Žurnal)
Nonspecific vaginitis is one of the most common problems in women of reproductive age, which ranks first in the structure of gynecological diseases and tends to increase. It is known that one of the causes of nonspecific vaginitis is the chronic stress influence on a woman’s body. At the same time, not only the hormonal system changes, but there is also a deficiency of trace elements, especially magnesium.